Assessment of energy expenditure, physical activity and sleep pattern in patients with frequent symptomatic ventricular ectopic beats - YILDIZ ÖZER, AYSEL (MASSON EDITEUR, 2016)
Background. Ventricular ectopic beats (VEBs) are considered as benign ventricular arrhythmias in patients without structural heart disease. However, symptomatic frequent VEBs can adversely affect energy metabolism. The present study aimed to determine the effect of symptomatic frequent VEBs on energy expenditure, physical activity and sleep pattern. Methods. Thirty-seven patients with symptomatic frequent VEBs and no structural heart diseases were enrolled. Patients underwent simultaneous 24-hour-ambulatory Holter electrocardiogram monitoring and the BodyMedia armband device monitoring which measures energy expenditure. Data acquired from both devices were compared with the data acquired from healthy volunteers in the control group. Results. Total energy expenditure (TEE) was higher in the patient group than the control group (1470 353 kcal vs 1125 275 kcal, P < 0.001). Average metabolic equivalence (aMETs) (1.1 +/- 0.2 vs. 1.3 +/- 0.2, P = 0.028), physical activity duration (PAD) (0.35 vs. 0.48, P = 0.007) and sleep duration (SDN) (3.15 vs. 4.31, P = 0.004) were significantly lower in the patient group than control group. VEBs frequency was inversely correlated with only SDN (r = 0.374, P = 0.027). Conclusion. Total energy expenditure (TEE) is increased in patients with symptomatic frequent VEBs in comparison with healthy subjects while PAD, average metabolic equivalence (aMETs) and SDN are decreased. VEBs frequency was inversely correlated with SDN. (C) 2016 Association pour le developpement de la recherche en nutrition (ADREN). Published by Elsevier Masson SAS. All rights reserved.
Keywords: Ventricular ectopic beats; Energy expenditure; Physical activity; APPARENT HEART-DISEASE; ADULTS